Identification of Indian mustard (Brassica juncea L.) varieties by DUS testing using morphological characters - Madhvi Tiwari,; V Bhushana Babu,; Nachiket Kotwaliwale,; Rajendra Hamad,; Karan Singh, (Journal of Oilseed Brassica, 2026)
Indian mustard [Brassica juncea (L.) Czern & Coss.] varieties were identified through distinctiveness,uniformity and stability (DUS) testing protocol on the basis of experiment conducted during 2013-14 and2014-15 consecutive years. The experimental procedure was carried as per official guideline of Indian mustard(PPV & FRA, 2009). The selected mustard varieties were identified based on six morphological charactersthat had capability to separate varieties into groups. Further they were classified based on three qualitativecharacters viz., leaf hairiness, time of 50% flowering and maturity period, three quantitative characters viz.,number of siliqua on main shoot, seeds per siliqua, and weight of 1000 seeds. The varieties PCR-7, PusaJaikisan, RH-781 and CS-52 were identified separately on the basis of hairiness, number of siliqua on mainshoot and number of seeds per siliqua respectively. All the remaining varieties were classified into groupsbased on time of 50% flowering, maturity period and weight of 1000 seeds. Thus the present study concludesthat morphological characters of DUS protocol prove to be very useful and convenient for varietal identificationwhich in turn helps in maintenance of genetic purity of varieties.